Bacteria from nodules of Abrus mollis Hance: genetic diversity and screening of highly efficient growth-promoting strains - Cao, Kexin; Chen, Jianhua; Li, Qiuling; Gu, Peng; Li, Liangbo; Huang, Rongshao (Frontiers in Microbiology, 2024)
Introduction Abrus mollis Hance. (AM) is an important species used in southern Chinese medicine. It is mainly found in Guangdong and Guangxi provinces in China, and it is effective in the treatment of hepatitis. Endophytic bacteria are known to affect the growth and quality of medicinal plants. However, there are limited reports describing endophytic bacteria related to AM. Methods In the present study, Illumina-based 16S rRNA gene sequencing was used to investigate the endophytic bacterial communities of root nodules of AM at five sampling sites in Guangxi. In addition, 179 strains of endophytic bacteria were isolated and categorized into 13 haplotypes based on recA sequence analysis. Results The phylogeny of the 16S rRNA gene sequences revealed a predominance of nonrhizobial endophytes. Microbial diversity analysis showed that Proteobacteria was the dominant phylum in all samples, while Bradyrhizobium was the dominant genus in different samples. An efficient strain, Rhizobium tropici FM-19, was screened and obtained through greenhouse experiments. The AM plants inoculated with this strain showed the best growth performance and high nitrogen fixation and nodulation capacity. Notably, total phenols and total flavonoids, important active components in AM, increased by 30.9 and 42.7%, respectively, after inoculation with Rhizobium tropici FM-19. Discussion This study provides insights into the complex microbial diversity of AM nodules and provides strain information for the efficient cultivation of AM.